Global health trends of human papillomavirus‐associated oral cancer: A review - Kehinde Kazeem Kanmodi; Jimoh Amzat; Jacob Njideka Nwafor; Lawrence Achilles Nnyanzi (Wiley, 2023)
Abstract Oral cancer is a malignant neoplastic disease, it constitutes the most common cancer in the head‐and‐neck region, and it is the 16th most common and 15th deadliest cancer type affecting humans. Despite the global efforts channelled towards global cancer control, the burden of oral cancer is still increasing. Every year, several thousands of people across 195 countries/territories die of oral cancer, and only about 40%-50% of the victims of oral cancer barely survive for 5 years after diagnosis. Within the past few decades, there has been a paradigm shift in the epidemiological trend of oral cancer risk factors. Oral sex - a major route of transmission of human papillomavirus (HPV) - was found to be increasing at an alarming rate, whereas tobacco and alcohol use had been on the decline. This narrative review critically discussed the contemporary challenges facing the global eradication of HPV‐associated oral cancer, with reasonable recommendations. The challenges discussed in this review are major, ranging from clinical to public health policy issues, which include the lack of validated and inexpensive oral HPV screening and diagnostic tools, high global public illiteracy on oral HPV infection, diverse sociocultural factors, weak global research capacity on oral HPV infection and HPV‐associated oral cancer and the absence of policies across different countries on national preventive programmes on HPV‐associated oral cancer. This review also identified the need for more attention towards the prevention and control oral HPV infection and HPV‐associated oral cancers globally.